Yang-Yin-Jie-Du decoction overcomes gefitinib resistance in non-small cell lung cancer via down-regulation of the PI3K/Akt signalling pathway - Shu-yi Chen; Gao-; Qi-jin Shu (Taylor & Francis Group, 2021)
Context Yang-Yin-Jie-Du Decoction (YYJDD) was used to improve gefitinib efficacy in our clinical practice, but its mechanism remains unclear. Objective This study explored if YYJDD could reverse gefitinib resistance. Materials and methods H1975 cells were exposed to control, 10 μM gefitinib, 3.2 mg/mL YYJDD or combination treatment. Cell viability was detected by MTT during 0-96 h. Apoptosis and the PI3K/Akt proteins were tested by flow cytometry and western-blot at 24 h. LY294002 was applied to further determine the role of the PI3K/Akt. 23 BALB/c nude xenograft mice received normal saline (n = 5), 80 mg/kg gefitinib (n = 6), 2.35 g/kg lyophilised powder of YYJDD (n = 6) or combination treatment (n = 6) by gavage for 4 weeks and submitted to TUNEL, immunohistochemistry, and western-blot. Results In vitro, gefitinib (IC50: 20.68 ± 2.06 μM) and YYJDD (IC50: 6.6 ± 0.21 mg/mL) acted in a moderate synergistic way. Combination treatment inhibited cell viability from 100% to 25.66%. Compared to gefitinb (33.23 ± 3.99%), cell apoptosis was increased with combination treatment (54.11 ± 7.32%), accompanied by down-regulation of the PI3K/Akt. LY294002 further inhibited cell viability, increased apoptosis, and down-regulated p-Akt/Akt. In vivo, the tumour sizes in the combination group (1165.13 ± 157.79 mm3) were smaller than gefitinib alone (1630.66 ± 208.30 mm3). The positive rate of TUNEL staining was increased by combination treatment (22.33 ± 2.75%) versus gefitinib (7.37 ± 0.87%), while the PI3K/Akt was down-regulated. Discussion and conclusion YYJDD has potential to overcome gefitinib resistance. Future investigations should be focussed on its specific targets.